Jordan's International Reserve Position : Justifiably Strong - Watt, Stanley (IMF Working Papers; Working Paper, 2007)
Jordan has seen a large increase in its international reserve holdings in recent years. While a healthy reserve buffer is needed under a fixed exchange rate regime, determining optimal reserve levels is not straightforward. In this paper, we first use several traditional measures of reserves adequacy to compare Jordan's reserve holdings with other emerging market (EM) countries. Subsequently, we analyze Jordan's reserve holdings using a reserves-optimizing model, based on Jeanne and Ranciere (2006) (J-R), but extended to allow reserve holdings to influence the likelihood of a sudden stop. The overall analysis suggests that Jordan's reserve holdings provide sufficient support to sustain the dinar peg and to deal with the most extreme capital account disruptions.